2022
DOI: 10.1111/cga.12458
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of viral infections in miscarriage and insights into the underlying molecular mechanisms

Abstract: Intrauterine viruses can infect the decidua and placenta and cause adverse effects on the fetus during gestation. This review discusses the contribution of various viral infections to miscarriage and the molecular mechanisms by which viruses can cause devastating effects on healthy fetuses and induce miscarriage. Severe acute respiratory syndrome coronavirus 2 as newly emerged coronavirus was considered here, due to the concerns about its role during pregnancy and inducing miscarriage, as well.In this narrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 136 publications
(164 reference statements)
0
7
0
1
Order By: Relevance
“…The literature is inconsistent in terms of reporting an association between pregnancy loss and HSV-2. A recently published review discussed the possible role of HSV-2 in miscarriage ( 26 ). A conclusion about this conflict could be crucial to further aid patients going through fertility treatment to avoid any possible pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
“…The literature is inconsistent in terms of reporting an association between pregnancy loss and HSV-2. A recently published review discussed the possible role of HSV-2 in miscarriage ( 26 ). A conclusion about this conflict could be crucial to further aid patients going through fertility treatment to avoid any possible pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
“…Possible suggestions include utero-placental dysfunction predisposing some women to adverse fetal outcomes including early pregnancy loss and stillbirth 36 . Infections can increase risk of early pregnancy loss and stillbirth, infecting the fetus via the placenta 37 with many infections asymptomatic. Fetal chromosomal abnormalities are the most common cause of early pregnancy loss in the first trimester, accounting for 50% of non-recurrent pregnancy losses 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of potential explanations for how pandemic mitigation measures could plausibly contribute to a modest decreased risk of miscarriage. For example, certain infectious diseases are associated with an increased risk of miscarriage 26 , and a reduced number of social contacts (as a result of pandemic restrictions) may have led to fewer infections (not only COVID-19) among pregnant women. It is also possible that pandemic restriction measures resulted in less physical stress, which again could have reduced women’s risk of miscarriage, although the impact on work-related physical strain on the risk of miscarriage is likely to be modest 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural measures indicated that the strict lockdowns of Denmark and Norway resulted in more drastic behavioural changes than in Sweden 24 . We hypothesized that the pandemic mitigation measures could plausibly decrease the risk of fetal death, as pregnant women were likely to have less exposure to infections 25 , 26 .…”
mentioning
confidence: 99%